2022
DOI: 10.1039/d2qi00869f
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase PdCu nanoparticles with improved C1 selectivity in ethanol oxidation

Abstract: PdCu/CNT-300 catalysts with a mixed crystalline phase were successfully prepared. The introduction of Cu elements and the presence of a phase interface in the mixed phase facilitated electron transfer and increased the rate of the EOR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Beyond the phase transitions between individual crystal phases, the unique interface effects arising from mixed crystal phases offer a promising avenue for catalyst optimization. Mixed crystal phases refer to structures containing two or more crystal phases within the same sample, and their realization can be achieved through diverse methods, such as temperature or pressure adjustment, solvothermal reactions, electrodeposition, and electron beam irradiation. , The mixing of crystal phases has the capacity to induce changes in the electronic structure of metal atoms, fine-tune the filling of d-band electrons, and optimize adsorption properties. , For instance, in the context of metal oxides, the lattice mismatch at the interface of mixed crystal phases can generate a significant number of oxygen vacancies, leading to heightened catalytic activity. , In the case of semiconductor materials, the presence of heterojunctions can exert a substantial influence on optical properties, effectively suppress electron–hole recombination, and facilitate the transfer of photogenerated electrons to reactive sites. This, in turn, contributes to the stabilization of charge separation efficiency and the enhancement of catalytic activity. ,, The field of crystal-phase engineering offers a versatile toolkit for modifying the photocatalytic performance of pristine semiconductors .…”
Section: Structure–activity Relationship Of Crystal-phase Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the phase transitions between individual crystal phases, the unique interface effects arising from mixed crystal phases offer a promising avenue for catalyst optimization. Mixed crystal phases refer to structures containing two or more crystal phases within the same sample, and their realization can be achieved through diverse methods, such as temperature or pressure adjustment, solvothermal reactions, electrodeposition, and electron beam irradiation. , The mixing of crystal phases has the capacity to induce changes in the electronic structure of metal atoms, fine-tune the filling of d-band electrons, and optimize adsorption properties. , For instance, in the context of metal oxides, the lattice mismatch at the interface of mixed crystal phases can generate a significant number of oxygen vacancies, leading to heightened catalytic activity. , In the case of semiconductor materials, the presence of heterojunctions can exert a substantial influence on optical properties, effectively suppress electron–hole recombination, and facilitate the transfer of photogenerated electrons to reactive sites. This, in turn, contributes to the stabilization of charge separation efficiency and the enhancement of catalytic activity. ,, The field of crystal-phase engineering offers a versatile toolkit for modifying the photocatalytic performance of pristine semiconductors .…”
Section: Structure–activity Relationship Of Crystal-phase Engineeringmentioning
confidence: 99%
“…Mixed crystal phases refer to structures containing two or more crystal phases within the same sample, and their realization can be achieved through diverse methods, such as temperature or pressure adjustment, solvothermal reactions, electrodeposition, and electron beam irradiation. 300,301 The mixing of crystal phases has the capacity to induce changes in the electronic structure of metal atoms, fine-tune the filling of d-band electrons, and optimize adsorption properties. 46,163 For instance, in the context of metal oxides, the lattice mismatch at the interface of mixed crystal phases can generate a significant number of oxygen vacancies, leading to heightened catalytic activity.…”
Section: Structure−activity Relationship Of Crystal-phase Engineeringmentioning
confidence: 99%
“…Recent studies have shown that one of the key factors affecting the catalytic efficiency of palladium-based nanocatalysts is the catalytic active site on the catalyst surface, and the catalytic efficiency of palladium-based catalysts can be greatly improved by constructing abundant catalytic active sites . The introduction of defects in palladium-based nanocatalysts is the most direct way to construct catalytic active sites. And among the different types of defects introduced, interfacial defects in the construction of heterogeneous structures show unique advantages. The palladium atoms at interfacial defects have more uncoordinated bonds and high surface energy, which can effectively strengthen the interaction between palladium atoms and alcohol molecules so that alcohol molecules are more easily adsorbed on the surface of palladium atoms, thus improving the catalytic efficiency. , However, at present, the conditions for constructing such multiphase interfacial palladium-based catalysts are harsh, and the steps are complicated. Furthermore, the synthesized multiphase structures have poor controllability.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 However, the currently used catalysts for the above reactions exhibited limited conversion efficiency. In light of this, it is crucial to develop cost-effective, stable and highly efficient catalysts to enable broader applications of the EOR and 4-NP reduction.Interestingly, Pd-based catalysts, such as PdCu, 12,13 PdNi, 14,15 and PdW, 16,17 etc. have emerged as excellent candidates for the EOR and 4-NP reduction.…”
mentioning
confidence: 99%
“…Interestingly, Pd-based catalysts, such as PdCu, 12,13 PdNi, 14,15 and PdW, 16,17 etc. have emerged as excellent candidates for the EOR and 4-NP reduction.…”
mentioning
confidence: 99%